A new subtropical species of goby of the genus Luciogobius (Gobiidae) from southwestern Japan - Koreeda, Reo; Maeda, Ken; Motomura, Hiroyuki (Zootaxa, 2023)
Luciogobius griseus n. sp., belonging to the Luciogobius platycephalus complex, is described on the basis of 40 specimens from the Nansei Islands, southwestern Japan (subtropical area). The new species is generally found in intertidal gravel sediments subjected to freshwater runoff from springs on coastal lines or river mouths and is characterized by the following combination of characters: total second dorsal-fin rays 9–12 (modally 11); total anal-fin rays usually 12–14 (modally 13); pectoral-fin rays 12–15 (modally 13); vertebrae 17 or 18 + 23 or 24 = 40–42 (18 + 23 = 41); uppermost 2–4 (2–3) rays on pectoral fin free; 8–12 pectoral-fin rays branched (uppermost free rays and sometimes lowermost ray unbranched); pectoral-fin membrane not strongly concave anteriorly (except for free rays); pelvic fins united, forming a disk; head relatively short, 13.9–20.8% of standard length (SL); relatively short pre-pelvic fin, length 14.4–22.1% of SL; relatively long pre-dorsal fin, length 68.9–72.9% of SL; relatively long pre-anal fin, length 63.5–67.7% of SL; relatively short pelvic fin, length 2.8–4.7% of SL; distance between posterior end of pelvic fin and anus relatively long, 32.0–36.4% of SL (aforementioned morphometrics each distinguishing L. griseus n. sp. from other species in the L. platycephalus complex); and fresh specimens with greenish dark brown or gray body. A key to the L. platycephalus complex is provided, together with limited descriptions and remarks on the other two members of the complex.